Venting: A Guide to Releasing Reef Fish with Ruptured Swimbladders - John Stevely; Don Sweat; Chuck Adams; Rich Novak (EDIS, 2007)
SGEF-162, a 2-page full-color brochure by John Stevely, Don Sweat, Chuck Adams, Rich Novak, provides a step-by-step guide to how to vent reef fish, and describes the venting tools available to fishermen today. Published by the UF Sea Grant College Program, January 2005.